Legume Crops [Working Title] 2020
DOI: 10.5772/intechopen.91857
|View full text |Cite
|
Sign up to set email alerts
|

Helping Legumes under Stress Situations: Inoculation with Beneficial Microorganisms

Abstract: In the upcoming years, legume crops will be subjected to multiple, diverse, and overlapping environmental stressors (raise in global temperatures and CO 2 , drought, salinity, and soil pollution). These factors will menace legume productivity and food quality and security. In this context, tolerant plant growth promoting rhizobacteria (PGPR) are useful biotechnological tools to assist legume establishment and growth. In this chapter, tolerant PGPR able to promote legume growth will be revised. Besides, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…It is important to notice that metals content in shoots were below the values allowed for human or animal consumption, whose limits are 30 ppm As, 10 ppm Cd, 40 ppm Cu and 500 ppm Zn [10,19]. These results are in consonance with previous works indicating that nitrogen-fixing bacteria and endophytes inside nodules reduce metal translocation to legume shoots in metal contaminated soils and increase the phytostabilization potential of the plant [19,38].…”
Section: Discussionsupporting
confidence: 84%
“…It is important to notice that metals content in shoots were below the values allowed for human or animal consumption, whose limits are 30 ppm As, 10 ppm Cd, 40 ppm Cu and 500 ppm Zn [10,19]. These results are in consonance with previous works indicating that nitrogen-fixing bacteria and endophytes inside nodules reduce metal translocation to legume shoots in metal contaminated soils and increase the phytostabilization potential of the plant [19,38].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, phosphate solubilization, IAA, and siderophores production may also account for the improvement of legume-rhizobium interactions and plant tolerance to abiotic stress [82][83][84][85]. Plant hormones are known to play an essential role in plant-microorganism interactions, including in the regulation of symbiotic legume-rhizobium interactions and root nodule organogenesis [86].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that single and combined inoculation of common bean with Rhizobium tropici , Trichoderma asperellum , and plant growth promoting microorganisms (PGPM, e.g. Burkholderia and Bacillus subtilis ) increased the number of nodules, shoot and root biomass accumulation and improved yield components as well (Gabre et al, 2020; Abd El & Azeem, 2022; Navarro‐Torre et al, 2020). Additionally, Figueiredo et al (2008) reported that co‐inoculation of Rhizobium and Paenibacillus polymyxa strains on common bean mitigated some of the negative effects of DS increasing the plant growth, nitrogen content, and nodulation.…”
Section: Introductionmentioning
confidence: 99%